The Covid‐19 app and the fire spirit: Receiving messages in Britain and Siberia. Issue 6 (1st December 2021) - Laptander, Roza; Vitebsky, Piers
Abstract : The UK's National Health Service Covid‐19 'track and trace' app was designed as a critical public health technology. So why has it encountered so much resistance? The authors compare alerts on the phone regarding exposure to possible Covid‐19 infection with messages from a Siberian nomad's domestic fire, which sometimes crackles warnings of potential illnesses or accidents. Though these prediction technologies may seem radically different, they are both instruments for thinking about possible futures and adjusting behaviour. The authors interpret them as forms of divination that differ not so much in their logic as in their embeddedness in wider cosmologies of person, fate and society. The Siberian fire generates meaning as a focal point of coherence within many narrative strands concerning family and landscape; acceptance of its messages is rooted in intimacy and entanglement. This highlights how the Covid‐19 app belongs to a state of emergency and exception. Its statistical idiom of risk and its culturally hyper‐valued focus on privacy conceal the identities of people caught in the chain of infection, blocking social and narrative coherence and thereby encouraging suspicion and cynicism.